2018
DOI: 10.3389/fimmu.2018.02563
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome-Independent Role of NLRP3 Mediates Mitochondrial Regulation in Renal Injury

Abstract: The NOD-like receptor family, pyrin domain containing-3 (NLRP3) inflammasome has been implicated in renal inflammation and fibrosis. However, the biological function of inflammasome-independent NLRP3 in non-immune cells is still unclear. We evaluated the role of inflammasome-independent NLRP3 in renal tubular cells and assessed the value of NLRP3 as a therapeutic target for acute kidney injury (AKI). Various renal tubular cell lines and primary cultured tubular cells from NLRP3 knockout (KO) mice were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 40 publications
9
120
2
1
Order By: Relevance
“…B, Representative bands of western blot analysis for the expression of EZH2 and bar graph showed the quantification, n = 3; Two-tailed t test was used for the statistical analysis; Values are expressed as the mean ± SEM. 23,25,31,32 At the cellular level, our further study revealed that the ablation of ROS with NAC abolished H/Rmediated elevation of pyroptosis-related protein expression and caspase-1 activity, and the induction in pyroptotic cells and LDH release strongly confirmed that pyroptosis was inhibited by decreased ROS generation. C-J, HK-2 cells were transfected with an siRNA against EZH2 or a negative control siRNA (si-NC) for 48 h and were pretreated with or without DZNeP at dose of 2.5 μM for 1 h before being exposed to H/R.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…B, Representative bands of western blot analysis for the expression of EZH2 and bar graph showed the quantification, n = 3; Two-tailed t test was used for the statistical analysis; Values are expressed as the mean ± SEM. 23,25,31,32 At the cellular level, our further study revealed that the ablation of ROS with NAC abolished H/Rmediated elevation of pyroptosis-related protein expression and caspase-1 activity, and the induction in pyroptotic cells and LDH release strongly confirmed that pyroptosis was inhibited by decreased ROS generation. C-J, HK-2 cells were transfected with an siRNA against EZH2 or a negative control siRNA (si-NC) for 48 h and were pretreated with or without DZNeP at dose of 2.5 μM for 1 h before being exposed to H/R.…”
Section: Discussionsupporting
confidence: 58%
“…15,16 Structural damage of renal tubules is induced by I/R injury via triggering renal inflammatory responses. 23 However, whether EZH2 is linked to Nox4-mediated ROS generation and activation of pyroptosis still remains to be unknown in renal I/R injury. [17][18][19] Oxidative stress, a pathological phenomenon in which the generation of reactive oxygen species (ROS) surpasses the capacity of endogenous antioxidant systems, always causes renal tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…For detecting tissue protein expression, immunohistochemistry was performed [40]. To demonstrate fibrosis, liver sections were stained 2 h with Masson's trichrome reagent [41].…”
Section: Histological Analysismentioning
confidence: 99%
“…69 In keeping with the assertion that loss of membrane potential is a consequence rather than cause of NLRP3 activation, another study reported that NLRP3 deficiency in renal tubular cells protected mitochondria against depolarisation during hypoxia. 79 The above models may not be mutually exclusive; it is possible that an early loss of mitochondrial membrane integrity results in just enough externalised mtDNA to participate in NLRP3 signalling, which then drives further mitochondrial damage. In line with this, one study examining temporal changes in mitochondrial stability during NLRP3 activation reported that LPS-primed BMDMs treated with ATP or nigericin exhibited some inflammasome-independent mitochondrial hyperpolarisation at early time points (up to 15 min post treatment).…”
Section: Nlrp3 a Cytosolic Sensor For Mtdna?mentioning
confidence: 99%